Identificación de los factores de riesgo químico y biológico y la salud del talento humano del Gad de la provincia de Cotopaxi. Manual de procedimientos de seguridad para riesgos químicos y biológicos. - Herrera García, Felipe Centurión (2016)
This research identifies and assesses the level of chemical and biological risks to which workers of Provincial Decentralized Autonomous Government of Cotopaxi are exposed, using qualitative-quantitative evaluation methods endorsed by the National Institute of Safety and Occupational Health in Spain, with the aim of documenting the presence of risks, levels are and determine the checkpoints. Research based on the regulations of legal texts that govern the occupational safety and health, applicable to all public and private institutions, determining that moderate chemical risk for workers of workshops and a biological intervention level for N1H1 virus exist. The methodology applied is bibliographic documentary, field and observation; the type of research is a feasible project. The results were to design a procedure manual for chemical and biological risks, allowing this institution to comply as provided for in the legislation on health and safety.